2018
DOI: 10.3390/agriculture8120191
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Market Power Along Food Supply Chains: Evidence and Methodological Insights from the Fluid Milk Sector in Italy

Abstract: Concerns about the functioning of food supply chains have been raised by the European Commission over past years, calling for more effective and coordinated action by National Competition Authorities (NCAs). To fill this knowledge gap, an equilibrium displacement model is used to screen conduct along the supply chain, combining the advantages of asymmetric price transmission (APT) studies and structural models. The test was carried out on the Italian fluid milk supply chain following market monitoring action b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Results indicate that the pasta chain in Italy is characterised by asymmetry in price transmission. As discussed in Sections 1 and 2, this may have several causes, but it is often considered as an indication of power imbalances along the chain [3,6,12,79]. Our analyses highlight how the retail sector seems to act as a price shock absorber, but how there is an asymmetry in the transmission of price rises and falls.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Results indicate that the pasta chain in Italy is characterised by asymmetry in price transmission. As discussed in Sections 1 and 2, this may have several causes, but it is often considered as an indication of power imbalances along the chain [3,6,12,79]. Our analyses highlight how the retail sector seems to act as a price shock absorber, but how there is an asymmetry in the transmission of price rises and falls.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies have focused on milk-related chains. Cavicchioli [12] and Madau et al [56] studied the buyer power in the supply chain of fresh milk highlighting how market structure affects the upstream and downstream spread of prices. Antonioli et al [57] analysed the differences along quality differentiated chains focusing on conventional and organic milk, finding that the latter chain is more responsive than the conventional one.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Serra and Goodwin () found symmetric adjustment in highly perishable dairy products in Spain despite a highly concentrated retail level. Concerning the Italian fluid milk sector, Cavicchioli () and later Madau, Furesi, and Pulina () detected the exertion of market power from retailing toward farmers along the fluid milk supply chain. The results obtained by Sckokai et al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent works have demonstrated that retail prices may vary largely as a consequence of dynamic pricing strategies on the part of retailers or manufacturers determining important consequences in the mechanism of price transmission along food supply chains (Ciapanna and Colonna 2011;Cacchiarelli et al 2016;Cavicchioli 2018). In the face of changing supply, the price-fixing decision of the distributor may also depend on the risk, measured by the relationship between demand elasticity and variable costs, as a result of uncertainty in consumer response to price variations (Perez-Mesa et al 2010).…”
Section: Introductionmentioning
confidence: 99%